Aesthetic and Functional Reconstruction of Large Lower Lip Defects with Depressor Anguli Oris Flap: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Lower Lip Cancer, Depressor Anguli Oris Flap, Adequate Mouth Opening